Plan estratégico de marketing para la empresa “Olimpia Sport”, de la ciudad de Loja - Calva Bravo, Richard Nixon (2016)
The overall objective of this thesis is to establish marketing strategies for the company Olimpia Sport city of Loja. This study considered the corresponding conceptual elements that are most important and the literature base for the development of this research. Among the materials and methods ; started with the Scientific Method which helped to describe and analyze the facts and events that occurred in the empresa Olimpia Sport for diagnosis of the current situation being experienced by the company, which was the basis , both in theory and in practice during the research process of this thesis , the deductive method was used to analyze data from general about the Strategic Marketing Plan for the company Olympia Sport and suggest the proposal under consideration , the inductive method was used to determine the results project , the same that were obtained through the techniques applied , in order to be able to determine the various functions and activities performed by officers and employees of the company Olimpia Sport , object study, Analytical Method , which allowed to undertake a situational analysis of the company performing strategies for achieving the objectives ; within the techniques were surveyed customers on a sample of 400 surveys, a survey of 10 employees and an interview with the company manager Olimpia Sport , under these conditions the data collaborated to develop the strengths, opportunities , weaknesses and threats , always relying on field research in the design of the SWOT matrix. Then internal and external analyzes were performed by applying the EFE and IFE Matrix to clearly identify the problems and the current status of the company Olimpia Sport. With these considerations by High Impact Matrix SWOT, four objectives, among which we were raised, making an advertising plan to present the products on the market, which will be made by radio, print and business cards and will cost $ 1,415. Implement a plan to increase sales promotions , for which will be sent to make hats , keychains , bags and end of year raffle for customers, all of this will cost $ 3750 . Conduct a training program for the sales staff, this will cost $ 959, and develop a marketing plan to achieve a position in the market at a cost of $ 350, these objectives as they cost a $ 6465 U.S. dollars. Based on interviews and surveys, managers, employees and customers of the company Olimpia Sport, is determined to not have a marketing plan, which improves the product to customers and provide better service. Finally put into consideration the findings and recommendations needed for the success of the proposal.